MISTIFIKASI RITUAL SISTEM PERTANIAN TRADISIONAL MASYARAKAT AJATAPPARENG, SULAWESI SELATAN - Nani Somba; Syahruddin Mansyur; Muhammad Nur (WalennaE, 2019)
The Ajatappareng region is known as the most important rice producer in South Sulawesi. Historical sources and archaeological evidence show that agricultural tradition in this region has been going on for at least the 14th century. In that time span, the Ajatappareng community carried out an agricultural system as a system of knowledge passed down from generation to generation. This study aims to obtain a record of knowledge related to the traditional farming system of the Ajatappareng community. It used etnographic method with data collection techniques through in-depth interviews and literature studies. The data obtained illustrates the belief system in the traditional farming system of the Ajatappareng community that has various stages and processes. This belief system is illustrated throught a series of rituals that become an integral part of Ajatappareng community’s agricultural system. In the process, this agricultural system has undergone various changes along with the development of knowledge. The recording of knowledge about agricultural traditions, belief system and the changes that surround them are important given the global trend that promotes sustainable food agriculture management.  Wilayah Ajatappareng dikenal sebagai penghasil beras paling utama di Sulawesi Selatan. Sumber-sumber sejarah dan bukti-bukti arkeologi yang ada menunjukkan bahwa tradisi pertanian di wilayah ini telah berlangsung setidaknya sejak abad ke-14. Sejak itu pula, masyarakat Ajatappareng menjalankan sistem pertanian sebagai pengetahuan yang diwariskan secara turun temurun. Penelitian ini bertujuan untuk menjelaskan pengetahuan terkait sistem kepercayaan dalam pertanian tradisional masyarakat Ajatappareng. Penelitian menggunakan metode etnografi dengan teknik pengumpulan data melalui wawancara mendalam dan diikuti studi literatur. Sistem pertanian tradisional masyarakat Ajatappareng memiliki berbagai tahapan dan proses, pengetahuan masyarakat tidak hanya masalah teknis, tetapi juga menyangkut sistem kepercayaan yang diwujudkan melalui rangkaian ritual. Sistem pertanian ini telah mengalami berbagai perubahan seiring dengan perkembangan pengetahuan masyarakat. Rekaman pengetahuan tentang tradisi pertanian, sistem kepercayaan, serta perubahan-perubahan yang melingkupinya, menjadi penting mengingat tren global yang mengedepankan pengelolaan kawasan pertanian pangan berkelanjutan.